Answer:
Part B: [tex]\displaystyle [1, 2][/tex]
Part A: Set both equation equal to each other by Substitution, since our y-values are already given to us.
Step-by-step explanation:
6x - 4 = 5x - 3
- 6x + 3 - 6x + 3
____________
[tex]\displaystyle -1 = -x; 1 = x[/tex]
Plug this coordinate back into the above equations to get the y-coordinate of 2.
y = mx + b [where b is the y-intercept and the rate of change (slope) is represented by m]
[tex]\displaystyle y = 5x - 3; [0, -3]; 5 = m \\ y = 6x - 4; [0, -4]; 6 = m[/tex]
I am joyous to assist you at any time.